Histomorphometrical Evaluation of Mice Testicular Tissue Following Short and Long-Term Administration of Clenbuterol: Testicular damages after Clenbuterol consumption - Imani, Masoud; Kheirandish, Reza; Babaei, Homayoon; Azizi, Shahrzad; Shojaeepour, Saeedeh (Iranian Journal of Pharmaceutical Sciences, 2023)
The aim of this study was to investigate the effects of long-term administration of clenbuterol on the histomorphometry and histopathology of testicular tissue in mice. 30 male NMRI mice were divided into three groups including the control group that received (0.1 ml of normal saline) the second group, (2.5 mg /kg clenbuterol) and the third group (8 mg/kg clenbuterol) that received for 30 consecutive days. At the days 3 and 30 from the beginning of the study, five mice were randomly sacrificed from each experimental group. The testicular tissue was removed from the right testis and fixed in the Bouin's solution for histomorphometric and pathological examinations. Degenerative lesions including distortion of the germ cells, reducing their number, and presence of vacuoles within the seminiferous epithelium were demonstrated in the clenbuterol treated groups. At the present study, administration of clenbuterol decreased spermatogenesis parameters including meiosis index, Johansen score, spermatogenesis percentage, seminiferous tubules diameter and epithelium height of seminiferous tubules both in the day 3 in low and high dose of clenbuterol with more severity in high dose. On the 30th day, testicular degenerative changes due to clenbuterol were more in the low dose of rather than high dose. According to the obtained results, it can be concluded that administration of clenbuterol may has potentially negative affect on the sperm production and fertility in male mice.